Method for preparing magnetic biochar composite material through coprecipitation method and application of magnetic biochar composite material

The co-precipitation method loads ferrous sulfate heptahydrate onto biochar to form a magnetic biochar composite material, which solves the problem of insufficient removal ability of traditional biochar for hexavalent chromium, and achieves efficient removal and economical and feasible water treatment effects.

CN119500069APending Publication Date: 2025-02-25YULIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411898943.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The low number of active functional groups on the surface of traditional biochar materials leads to a limited removal ability of hexavalent chromium Cr(VI).

Method used

By co-precipitation method, ferrous sulfate heptahydrate was loaded onto biochar, and the pH value was adjusted by magnetic stirring and alkaline substances to form a magnetic biochar composite material.

Benefits of technology

The active functional groups on the surface of biochar are significantly increased, the removal efficiency of Cr(VI) is improved, and the solid-liquid separation efficiency is enhanced through magnetic modification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500069A_ABST
    Figure CN119500069A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a magnetic biochar composite material through a coprecipitation method and application, and belongs to the technical field of water treatment. Comprising the following steps: S1, sequentially cleaning, chopping, drying, grinding and sieving biomass raw materials to obtain jujube branch biomass powder; s2, pyrolyzing the biomass powder in an N2 atmosphere to obtain biochar which is marked as BC; s3, an iron agent and distilled water are mixed, charcoal is added, and magnetic stirring is conducted; s4, adding an alkaline substance into the mixed solution, adjusting the pH value, and stirring; the biochar is used as a carrier, the ferrous sulfate heptahydrate is loaded, and active functional groups on the surface of the biochar are effectively increased, so that the removal efficiency of Cr (VI) is remarkably improved, the composite material inherits the advantages of high adsorption performance and low cost of the biochar, the solid-liquid separation efficiency of the composite material in water treatment is enhanced through magnetic modification, and the composite material has a good application prospect. And the method has economic feasibility and environmental friendliness in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of water treatment technology, and more specifically, to a method for preparing a magnetic biochar composite material by a co-precipitation method and its application. Background Art

[0002] With the rapid advancement of industrialization, water pollution, especially heavy metal pollution, has become a global environmental challenge; heavy metal ions, especially chromium (Cr), are widely used in many industrial processes, such as electroplating, dye production, mineral extraction, and leather tanning. These industrial activities are often the main source of heavy metal pollution; in nature, chromium exists mainly in two forms: trivalent chromium Cr (III) and hexavalent chromium Cr (VI). Trivalent chromium is a relatively stable and less toxic form, while hexavalent chromium is a major hidden danger of environmental pollution due to its high toxicity and solubility. Hexavalent chromium can diffuse through water flow and quickly penetrate into water bodies, posing a serious threat to aquatic organisms; with the rapid development of my country's economy, the level of industrialization and mechanical manufacturing has been significantly improved, which in turn has promoted the progress of the mechanization level of the agricultural and forestry industry, forming a modern agricultural and forestry industry with advanced technology and higher efficiency. In this process, crop yields have increased, and the production of agricultural and forestry wastes such as walnut shells, sugarcane bagasse, orange peels, etc. has also increased accordingly. As a low-cost potential adsorbent material, these wastes, after being processed and prepared into biochar, have gradually gained attention in the adsorption field due to their advantages such as easy availability, low cost and environmental friendliness.

[0003] Compared with other materials, biochar has rich pore structure and functional groups, and exhibits strong adsorption capacity; although traditional biochar materials have the ability to adsorb and remove hexavalent chromium Cr(VI), due to the relatively low number of active functional groups on the surface of biochar materials, the ability to remove hexavalent chromium Cr(VI) is subject to certain limitations, and therefore it is necessary to improve biochar materials to improve water treatment efficiency.

[0004] In view of this, we propose a method and application of preparing magnetic biochar composite materials by co-precipitation. Summary of the invention

[0005] The purpose of the present application is to provide a method for preparing a magnetic biochar composite material by a co-precipitation method and its application, which solves the technical problem that the number of active functional groups on the surface of the biochar material is relatively low and the removal ability of hexavalent chromium Cr(VI) is subject to certain limitations, and achieves the technical effect of effectively increasing the active functional groups on the surface of the biochar, thereby significantly improving the removal efficiency of Cr(VI).

[0006] The present application provides a method for preparing a magnetic biochar composite material by a co-precipitation method, comprising the following steps:

[0007] S1, washing, chopping, drying, grinding and sieving the biomass raw materials in sequence to obtain jujube branch biomass powder;

[0008] S2, pyrolyzing the biomass powder under N2 atmosphere to obtain biochar, denoted as BC;

[0009] S3, mixing the iron agent and distilled water, adding biochar, and stirring magnetically;

[0010] S4, adding alkaline substances to the mixed solution, adjusting the pH value, and stirring;

[0011] S5, allowing the mixed solution to stand to allow the magnetic biochar composite material to precipitate;

[0012] S6. Filter, wash and dry the precipitate to obtain a magnetic biochar composite material, recorded as MBC.

[0013] As an optional solution of the technical solution of this application document, the biomass raw material is jujube tree branches, and the jujube tree branch powder is 80 mesh, and the iron agent is ferrous sulfate heptahydrate.

[0014] As an optional solution of the technical solution of this application document, the pyrolysis temperature is 400°C to 800°C.

[0015] As an optional solution of the technical solution of this application document, the pyrolysis temperature is 700°C.

[0016] As an optional solution of the technical solution of this application document, the mass ratio of the biochar to ferrous sulfate heptahydrate is 1:0.5 to 1:2.5.

[0017] As an optional solution of the technical solution of this application document, the mass ratio of the biochar to ferrous sulfate heptahydrate is 1:1.

[0018] As an optional solution of the technical solution of this application document, S2 includes the following steps:

[0019] S2.1. Pour the prepared biomass powder into a quartz boat;

[0020] S2.2, then placed in a tube furnace, adjusting the tube furnace heating rate to 5 ° C / min;

[0021] S2.3, the reaction temperature is raised to 400°C, 500°C, 600°C, 700°C, and 800°C in sequence, and the pyrolysis is carried out at a constant temperature for 2 hours;

[0022] S2.4. Naturally cool down to the greenhouse to obtain biochar precursor.

[0023] As an optional solution of the technical solution of this application document, S3 includes the following steps:

[0024] S3.1, mix ferrous sulfate heptahydrate and distilled water, seal with plastic wrap, and stir with a magnetic stirrer for 30 min at a stirring speed of 100-300 rpm;

[0025] S3.2. Add the biochar precursor obtained in step S2.4 to the mixed solution in step 3.1, and perform magnetic stirring for 30 minutes at a stirring speed of 100-300 rpm.

[0026] As an optional solution of the technical solution of this application document, step S4 includes the following steps:

[0027] S4.1. Prepare a certain amount of 5 mol / L NaOH solution;

[0028] S4.2, add 5 mol / L NaOH solution dropwise to the mixed solution in step 3.2 using a rubber-tipped dropper, ensuring that the dripping speed is constant;

[0029] S4.3. After the pH of the suspension is adjusted to 10.0-11.0, continue magnetic stirring for 30 min at a stirring speed of 100-300 rpm.

[0030] The present application also provides an application of the above-mentioned method for preparing a magnetic biochar composite material by the co-precipitation method, which is applied in water treatment technology to improve the Cr(VI) removal efficiency.

[0031] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:

[0032] This application uses biochar as a carrier and loads ferrous sulfate heptahydrate to effectively increase the active functional groups on the biochar surface, thereby significantly improving the removal efficiency of Cr(VI). This composite material not only inherits the high adsorption performance and low cost advantages of biochar, but also enhances its solid-liquid separation efficiency in water treatment through magnetic modification, making it more economically feasible and environmentally friendly in practical applications.

[0033] This application uses discarded jujube tree branches as biomass raw materials, which have a wide range of sources and low costs, and effectively realizes the resource utilization of waste; jujube tree branches as a biomass substrate not only reduces the cost of raw materials, but also meets the requirements of environmental sustainable development and reduces the pollution of agricultural waste to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The preparation process of the magnetically modified biomass composite material of this application;

[0035] Figure 2 N2 adsorption-desorption isotherms and pore size distribution of BC and MBC in this application;

[0036] Figure 3 XRD patterns of BC and MBC of this application;

[0037] Figure 4 FT-IR images of MBC before and after adsorption of Cr(VI) in this application;

[0038] Figure 5 Scanning electron micrographs of BC and MBC before and after removal of Cr(VI) for this application;

[0039] Figure 6 The hysteresis loop of MBC for this application;

[0040] Figure 7 The following are (a) the effect of different pH values ​​on the performance of hexavalent chromium and (b) the Zeta point diagram of MBC in this application; DETAILED DESCRIPTION

[0041] The present application is further described in detail below in conjunction with the accompanying drawings.

[0042] Embodiment 1

[0043] Reference Figure 1-Figure 7 The present application discloses a method for preparing a magnetic biochar composite material by a co-precipitation method, comprising the following steps:

[0044] S1, washing, chopping, drying, grinding and sieving the biomass raw materials in sequence to obtain jujube branch biomass powder;

[0045] S2, pyrolyzing the biomass powder under N2 atmosphere to obtain biochar, denoted as BC;

[0046] S3, mixing the iron agent and distilled water, adding biochar, and stirring magnetically;

[0047] S4, adding alkaline substances to the mixed solution, adjusting the pH value, and stirring;

[0048] S5, allowing the mixed solution to stand to allow the magnetic biochar composite material to precipitate;

[0049] S6. Filter, wash and dry the precipitate to obtain a magnetic biochar composite material, recorded as MBC.

[0050] Wherein, the S2 comprises the following steps:

[0051] S2.1. Pour the prepared biomass powder into a quartz boat;

[0052] S2.2, then placed in a tube furnace, adjusting the tube furnace heating rate to 5 ° C / min;

[0053] S2.3, the reaction temperature is raised to 400°C, and the pyrolysis is carried out at a constant temperature for 2 hours;

[0054] S2.4. Naturally cool down to the greenhouse to obtain biochar precursor.

[0055] Wherein, the biomass raw material is jujube tree branches, and the jujube tree branch powder is 80 mesh, and the iron agent is ferrous sulfate heptahydrate;

[0056] Wherein, the S3 comprises the following steps:

[0057] S3.1. Mix ferrous sulfate heptahydrate and distilled water, seal with plastic wrap, and stir with a magnetic stirrer for 30 min at a stirring speed of 100-300 rpm; wherein the mass ratio of the biochar to ferrous sulfate heptahydrate is 1:0.5;

[0058] S3.2. Add the biochar precursor obtained in step S2.4 to the mixed solution in step 3.1, and perform magnetic stirring for 30 minutes at a stirring speed of 100-300 rpm.

[0059] The step S4 comprises the following steps:

[0060] S4.1. Prepare a certain amount of 5 mol / L NaOH solution;

[0061] S4.2, add 5 mol / L NaOH solution dropwise to the mixed solution in step 3.2 using a rubber-tipped dropper, ensuring that the dripping speed is constant;

[0062] S4.3. After the pH of the suspension is adjusted to 10.0-11.0, continue magnetic stirring for 30 min at a stirring speed of 100-300 rpm.

[0063] Specifically, cut the jujube branches into small pieces, rinse them with deionized water several times, remove the surface dust, put them in an oven, and dry them at 65°C for six hours. After drying, crush them with a grinder and pass through an 80-mesh sieve; pour the prepared biomass powder into a 10mL quartz boat, then place it in a tubular furnace, adjust the heating rate of the tubular furnace to 5°C / min, raise the reaction temperature to 400°C in turn, pyrolyze at a constant temperature for 2h, and then naturally cool to a greenhouse to obtain a biochar precursor; then mix 1.39g of ferrous sulfate heptahydrate and 50mL of distilled water, seal them with plastic wrap, and stir with a magnetic stirrer for 30min; add 2.78g of biochar precursor to the mixed solution. The suspension was magnetically stirred for 30 minutes; a certain amount of 5 mol / L NaOH solution was then prepared; 5 mol / L NaOH was added dropwise to the mixed solution using a rubber dropper to ensure a constant dripping rate, and after the pH of the suspension was adjusted to 10.0-11.0, magnetic stirring was continued for 30 minutes; after the above operations were completed, the magnet was taken out, the suspension was sealed with plastic wrap and allowed to stand for 12 hours; after the reaction was completed, the magnetic biochar composite material A was obtained by suction filtration, washing, and drying, and stored in a sample bag for later use.

[0064] Embodiment 2

[0065] The difference from the first embodiment is that, S2 includes the following steps:

[0066] S2.1. Pour the prepared biomass powder into a quartz boat;

[0067] S2.2, then placed in a tube furnace, adjusting the tube furnace heating rate to 5 ° C / min;

[0068] S2.3, the reaction temperature is raised to 800°C, and the pyrolysis is carried out at a constant temperature for 2 hours;

[0069] S2.4. Naturally cool down to the greenhouse to obtain biochar precursor.

[0070] Wherein, the biomass raw material is jujube tree branches, and the jujube tree branch powder is 80 mesh, and the iron agent is ferrous sulfate heptahydrate;

[0071] Wherein, the S3 comprises the following steps:

[0072] S3.1. Mix ferrous sulfate heptahydrate and distilled water, seal with plastic wrap, and stir with a magnetic stirrer for 30 min at a stirring speed of 100-300 rpm; wherein the mass ratio of the biochar to ferrous sulfate heptahydrate is 1:2.5;

[0073] S3.2. Add the biochar precursor obtained in step S2.4 to the mixed solution in step 3.1, and perform magnetic stirring for 30 minutes at a stirring speed of 100-300 rpm.

[0074] Specifically, cut the jujube branches into small pieces, rinse them with deionized water several times, remove the surface dust, put them in an oven, and dry them at 65°C for six hours. After drying, crush them with a grinder and pass through an 80-mesh sieve; pour the prepared biomass powder into a 10mL quartz boat, then place it in a tubular furnace, adjust the heating rate of the tubular furnace to 5°C / min, raise the reaction temperature to 800°C in turn, pyrolyze at a constant temperature for 2h, and then naturally cool to a greenhouse to obtain a biochar precursor; then mix 1.39g of ferrous sulfate heptahydrate and 50mL of distilled water, seal them with plastic wrap, and stir with a magnetic stirrer for 30min; add 0.55g of biochar precursor to the mixed solution. The suspension was magnetically stirred for 30 minutes; a certain amount of 5 mol / L NaOH solution was then prepared; 5 mol / L NaOH was added dropwise to the mixed solution using a rubber-tipped dropper to ensure a constant dripping rate, and after the pH of the suspension was adjusted to 10.0-11.0, magnetic stirring was continued for 30 minutes; after the above operations were completed, the magnet was taken out, the suspension was sealed with plastic wrap and allowed to stand for 12 hours; after the reaction was completed, the magnetic biochar composite material B was obtained by suction filtration, washing, and drying, and stored in a sample bag for later use.

[0075] Embodiment 3

[0076] The difference from the first embodiment and the second embodiment is that S2 includes the following steps:

[0077] S2.1. Pour the prepared biomass powder into a quartz boat;

[0078] S2.2, then placed in a tube furnace, adjusting the tube furnace heating rate to 5 ° C / min;

[0079] S2.3, the reaction temperature is raised to 700°C, and the pyrolysis is carried out at a constant temperature for 2 hours;

[0080] S2.4. Naturally cool down to the greenhouse to obtain biochar precursor.

[0081] Wherein, the biomass raw material is jujube tree branches, and the jujube tree branch powder is 80 mesh, and the iron agent is ferrous sulfate heptahydrate;

[0082] Wherein, the S3 comprises the following steps:

[0083] S3.1. Mix ferrous sulfate heptahydrate and distilled water, seal with plastic wrap, and stir with a magnetic stirrer for 30 min at a stirring speed of 100-300 rpm; wherein the mass ratio of the biochar to ferrous sulfate heptahydrate is 1:1;

[0084] S3.2. Add the biochar precursor obtained in step S2.4 to the mixed solution in step 3.1, and perform magnetic stirring for 30 minutes at a stirring speed of 100-300 rpm.

[0085] Specifically, cut the jujube branches into small pieces, rinse them with deionized water several times, remove the surface dust, put them in an oven, and dry them at 65°C for six hours. After drying, crush them with a grinder and pass through an 80-mesh sieve; pour the prepared biomass powder into a 10mL quartz boat, then place it in a tubular furnace, adjust the heating rate of the tubular furnace to 5°C / min, raise the reaction temperature to 700°C in turn, pyrolyze at a constant temperature for 2h, and then naturally cool to a greenhouse to obtain a biochar precursor; then mix 1.39g of ferrous sulfate heptahydrate and 50mL of distilled water, seal them with plastic wrap, and stir with a magnetic stirrer for 30min; add 1.39g of biochar precursor to the mixed solution. The suspension was magnetically stirred for 30 minutes; a certain amount of 5 mol / L NaOH solution was then prepared; 5 mol / L NaOH was added dropwise to the mixed solution using a rubber-tipped dropper to ensure a constant dripping rate, and after the pH of the suspension was adjusted to 10.0-11.0, magnetic stirring was continued for 30 minutes; after the above operations were completed, the magnet was taken out, the suspension was sealed with plastic wrap and allowed to stand for 12 hours; after the reaction was completed, the magnetic biochar composite material C was obtained by suction filtration, washing, and drying, and stored in a sample bag for later use.

[0086] The magnetic biochar composite material A, magnetic biochar composite material B and magnetic biochar composite material C prepared according to Example 1, Example 2 and Example 3 were tested for performance respectively. According to the test results, the magnetic biochar composite material C prepared according to Example 3 has more excellent performance. The following magnetic biochar composite material C (denoted as MBC) with better performance is taken as an example, which can be confirmed from the BET, XRD, FT-IR, SEM and VSM spectra of the magnetic biochar:

[0087] According to the specific surface area and pore structure data (Table 1, Figure 2 ) shows that the specific surface area of ​​MBC is 230.96 m2 / g, which is about three times that of BC, indicating that MBC can provide more adsorption sites than BC; Figure 2 As shown in the figure, the adsorption-desorption isotherms of BC and MBC are highly consistent with the type IV isotherm, and the pore size distribution analysis shows that the pore structure of both is mainly mesoporous; these results show that the magnetic modified biochar has been optimized in pore structure and may have obvious advantages in improving adsorption efficiency and selectivity;

[0088]

[0089] Table 1

[0090] According to the XRD patterns of BC and MBC (Appendix Figure 3 ) It can be seen that BC has two amorphous peaks at 2θ of 15-30° and 35-45°, indicating the presence of amorphous carbon; in addition, 29.2° is the diffraction peak of SiO2; after magnetization, the spectrum of MBC shows new characteristic diffraction peaks at 2θ of 18.3°, 30.2°, 35.6°, 43.2°, 53.7°, 57.2° and 62.9°, corresponding to XRD crystal planes (111), (220), (311), (400), (422), (511) and (440), respectively, which are consistent with Fe2O3 (PDF#39-1346); the above results show that the iron in biochar exists in the form of Fe2O3, indicating that iron is successfully loaded on biochar.

[0091] According to the infrared spectra of MBC before and after adsorption of Cr(VI) (Appendix Figure 4 ) It can be seen that the broadband at 3421cm-1 corresponds to the stretching vibration of the -OH group, the characteristic peak at 1623cm-1 is attributed to the stretching vibration of the -COOH group, the peak at 1390cm-1 corresponds to the CO vibration, and the vibration peak at 1110cm-1 corresponds to the CC bond, which are all characteristic absorption peaks of biochar; in addition, the absorption peak at 628cm-1 in the MBC spectrum corresponds to the Fe-O stretching vibration, indicating that FeSO4·7H2O is successfully loaded on biochar;

[0092] From the above analysis, it can be seen that magnetic modification has little effect on the functional group structure of biochar, and the MBC spectrum after the reaction found that the peak intensity of -OH, -COOH and Fe-O functional groups was significantly weakened, which indicates that -OH and -COOH functional groups may interact with Cr(VI) by forming complexes or surface complexes, while Fe-O functional groups may provide electrons for the reduction of Cr(VI) and promote the conversion of Cr(VI) to Cr(III); the synergistic effect of these functional groups may involve chemical adsorption, complexation, reduction and precipitation mechanisms, which jointly promote the effective removal of chromium.

[0093] According to the SEM images of BC and MBC at different magnifications (see Appendix Figure 5 ) It can be known that from Figure 5 a and Figure 5 b It can be observed that the surface of the unmodified biochar is smooth and has small particles attached to it, presenting a rod-like structure; Figure 5 c and Figure 5In d, the surface of biochar modified by FeSO4·7H2O is uneven, and Fe3O4 and Fe2O3 nanoparticles are loaded on the surface and in the pores of biochar. This structure provides abundant adsorption active sites. After adsorption, chromium ions enter the pores and fill the pores, thus changing the structure of MBC ( Figure 5 e and Figure 5 f), verifying the effectiveness of the adsorption process.

[0094] According to VSM (Appendix Figure 6 ) In practical applications, MBC can be quickly separated from the solution using a magnet. Its hysteresis loop is shown in Figure 6 As shown; it can be seen from the figure that the saturation magnetization of the MBC adsorbent is 16.6emu / g, which indicates that MBC can be quickly separated from the solution by applying an external magnetic field.

[0095] In summary, the analysis of BET, XRD, FT-IR, SEM and VSM diagrams of MBC shows that ferrous sulfate heptahydrate loaded jujube tree branch-based biochar significantly improves the physicochemical properties of MBC and enhances its surface activity and application potential.

[0096] Based on the above conclusions, a static batch experiment was conducted to explore the effects of pH value, different time, initial concentration and temperature on the performance of magnetic biochar in removing Cr(VI); the Cr(VI) solution was obtained by laboratory simulation, and the pH value was adjusted by HCl or NaOH solution; a certain amount of magnetic biochar was accurately weighed in a 250mL conical flask, and 100mL of Cr(VI) solution was added; the conical flask was placed in a shaker of a dual-function constant temperature water bath oscillator, and the removal experiment was carried out at 25℃ and 150r / min. The supernatant was filtered through a microporous membrane and the Cr(VI) concentration was determined using a visible ultraviolet spectrophotometer.

[0097] Specific research methods:

[0098] (1) Pour 50 ml (50 mg / L) of chromium experimental solution into a conical flask, adjust the pH value of the solution to 2 with 1 M HCl, and seal with plastic wrap;

[0099] (2) Place in a dual-function constant temperature water bath oscillator and oscillate for 3 h at a reaction temperature of 25°C and a rotation speed of 150 r / min;

[0100] (3) When the reaction reaches adsorption equilibrium, use a syringe to weigh 10 ml of water sample, filter it through a microporous filter membrane, and transfer 1 ml of the filtrate into a 50 ml colorimetric tube and dilute to the scale line;

[0101] (4) Then add 1+1 sulfuric acid and phosphoric acid, and then add 2 ml of diphenylcarbazide color developer solution, and shake well;

[0102] (5) After standing for 5 to 10 minutes, use a 3 cm cuvette and water as a reference to measure the absorbance at a wavelength of 540 nm using an ultraviolet spectrophotometer; thereby determining the concentration of hexavalent chromium, and the removal rate is calculated by the following formula:

[0103]

[0104] Wherein, R is the removal rate (%), Ci, Ce, qe, V, and W are the initial concentration (mg / L), equilibrium concentration (mg / L), equilibrium adsorption capacity (mg / g), volume (L), and adsorbent mass (g), respectively.

[0105] By attaching Figure 7 It can be seen that Cr(VI) in the solution changes with the pH value. When the pH value is 2-6.5, hexavalent chromium mainly exists in the form of HCrO4-, and when pH>6.5, hexavalent chromium mainly exists in the form of CrO42-; the pH value of the solution affects the surface charge of the material. Zeta potential measurement shows that MBC is positively charged at pH 2-4.7 and negatively charged at pH 4.7-11 ( Figure 7 b); The positively charged surface enhances the adsorption of HCrO4- due to electrostatic attraction, while the negatively charged surface hinders the removal efficiency of Cr(VI) due to electrostatic repulsion. Figure 7 As shown in Figure a, the efficiency of MBC in adsorbing Cr(VI) decreases significantly with the increase of pH; when the pH value is 2, the removal rate of hexavalent chromium will reach the maximum; this is because under acidic conditions, HCrO4- has a higher oxygen storage capacity and can adsorb more H+, and MBC and H+ can jointly adsorb Cr(VI) in the solution. As the pH value increases, the degree of protonation on the MBC surface will decrease, the concentration of OH- in the solution will increase, and the probability of hexavalent chromium being adsorbed will also decrease; therefore, under acidic conditions, the removal efficiency of MBC for Cr(VI) is significantly higher than that in alkaline environments.

[0106] In summary, the present application adopts ferrous sulfate heptahydrate loading technology to improve the activity of jujube tree branch-based biochar. This method enhances its adsorption capacity by loading ferrous sulfate heptahydrate onto jujube tree branch-based biochar.

Claims

1. A method for preparing a magnetic biochar composite material by coprecipitation, characterized in that: The following steps are involved: S1, washing, chopping, drying, grinding and sieving the biomass raw materials in sequence to obtain jujube branch biomass powder; S2, pyrolyzing the biomass powder under N2 atmosphere to obtain biochar, denoted as BC; S3, mixing the iron agent and distilled water, adding biochar, and stirring magnetically; S4, adding alkaline substances to the mixed solution, adjusting the pH value, and stirring; S5, allowing the mixed solution to stand to allow the magnetic biochar composite material to precipitate; S6. Filter, wash and dry the precipitate to obtain a magnetic biochar composite material, recorded as MBC.

2. The method for preparing a magnetic biochar composite material by coprecipitation according to claim 1, characterized in that: The biomass raw material is jujube tree branches, and the jujube tree branch powder is 80 meshes, and the iron agent is ferrous sulfate heptahydrate.

3. The method for preparing a magnetic biochar composite material by coprecipitation according to claim 1, characterized in that: The pyrolysis temperature is 400°C to 800°C.

4. The method for preparing a magnetic biochar composite material by coprecipitation according to claim 1, characterized in that: The pyrolysis temperature is 700°C.

5. The method for preparing a magnetic biochar composite material by coprecipitation according to claim 2, characterized in that: The mass ratio of the biochar to ferrous sulfate heptahydrate is 1:0.5 to 1:2.

5.

6. The method for preparing a magnetic biochar composite material by coprecipitation according to claim 2, characterized in that: The mass ratio of the biochar to ferrous sulfate heptahydrate is 1:

1.

7. The method for preparing a magnetic biochar composite material by coprecipitation according to claim 3, characterized in that: The S2 comprises the following steps: S2.

1. Pour the prepared biomass powder into a quartz boat; S2.2, then placed in a tube furnace, adjusting the tube furnace heating rate to 5 ° C / min; S2.3, the reaction temperature is raised to 400°C, 500°C, 600°C, 700°C, and 800°C in sequence, and the pyrolysis is carried out at a constant temperature for 2 hours; S2.

4. Naturally cool down to the greenhouse to obtain biochar precursor.

8. The method for preparing a magnetic biochar composite material by coprecipitation according to claim 7, characterized in that: The S3 comprises the following steps: S3.1, mix ferrous sulfate heptahydrate and distilled water, seal with plastic wrap, and stir with a magnetic stirrer for 30 min at a stirring speed of 100-300 rpm; S3.

2. Add the biochar precursor obtained in step S2.4 to the mixed solution in step 3.1, and perform magnetic stirring for 30 minutes at a stirring speed of 100-300 rpm.

9. The method for preparing a magnetic biochar composite material by coprecipitation according to claim 1, characterized in that: The step S4 comprises the following steps: S4.

1. Prepare a certain amount of 5 mol / L NaOH solution; S4.2, add 5 mol / L NaOH solution dropwise to the mixed solution in step 3.2 using a rubber-tipped dropper, ensuring that the dripping speed is constant; S4.

3. After the pH of the suspension is adjusted to 10.0-11.0, continue magnetic stirring for 30 min at a stirring speed of 100-300 rpm.

10. Application of the method for preparing magnetic biochar composite material by co-precipitation method according to any one of claims 1 to 9, characterized in that: Applied in water treatment technology to improve Cr(VI) removal efficiency.